Public Transit Loyalty Modeling Considering the Effect of Passengers’ Emotional Value: A Case Study in Xiamen, China - Shi-chao Sun (Journal of Advanced Transportation)
To better sustain passengers’ loyalty towards bus service, this paper addressed the modeling of the public transit loyalty by the use of structural equation model. As a novel hypothesis, the emotional value was considered to have effects on the perceived value of bus services in this study, which reflected the degree of passengers’ emotional dependence on the public transit. Specifically, in order to better assess the loyalty, seven unobserved variables were measured to construct the structural model, namely, “service guarantee,” “operational services and efficiency,” “emotional value,” “perceived value,” “expectation,” “satisfaction,” and “loyalty.” The goodness-of-fit of the model was estimated and evaluated by using the survey data harvested from Xiamen, China. Besides, the index score of variables was also computed to help determine targeted approaches to better improve the level of bus service. The results indicated that the time cost and the monetary cost actually had no effects on the perceived value of users in the case study. At the same time, however, it also proved that passengers’ emotional value towards the public transit indeed affected passengers’ perception of the service value. In addition, whether users’ perceived value was as expected determined how much passengers satisfied with the service. Regarding the index score of variables, it indicated a great dissatisfaction of passengers towards the current bus service. Unexpectedly, the score of loyalty even still retained a relatively high level, which reflected continue-to-use willingness of passengers. It implied that being subject to economic conditions and other factors, passengers were captive and had to continue relying on the public transit, in spite of their dissatisfaction. As for the improvement direction of bus services, targeted approaches should be determined to improve the quality of bus service, regarding the aspects of “condition of facilities in the bus,” “driving stability and comfort,” “vehicle speed,” and “safety.”